Moodle and how to organize an examination via net for special psychology in the faculty of engineering education - Hanoi University of Technology - Duong, Thị Kim Oanh; Tieu, Kim Cương; Nguyen, Thành Công (Journal of Technical Education Science, 2009)
In recent years, teachers and managers of education have paid special attention to the organization of university examinations via the net. This shows greater advantages than the traditional assessment methods. Nevertheless, most universities are facing difficulties in the choice of a suitable software and the way of organizing an examination using software. This paper deals with the Moodle and the way of organizing such an examination via the net, as applied to the subject of Special Psychology at the Faculty of Engineering Education from Hanoi University of Technology.